Self-emulsifying Drug Delivery System for Improvement of Solubility of Drug - Bhange, Manjusha (Asian Journal of Pharmaceutics (AJP), 2024)
In this review, we examine the solubility properties of compounds and the different ways to improve solubility for more efficient action. We also address the common variables that affect solubilities, such as polarity, polymorphs, molecular size, temperature, pressure, wildlife of the solute and flush, and particle scope. To overcome these solubility problems, various approaches have been taken to increase solubility. These include physical modification, chemical modification, and miscellaneous methods. One of the most efficient techniques we discuss is the Self- Emulsifying Medicine Transfer Scheme (self-emulsifying drug delivery system), which is suitable for emulsions with droplet sizes around 100 nm to 300 nm. We also discuss the further modification of SEDDS, which is the selfmicro blending medication transfer system (self-microemulsifying drug-delivery system). SMEDDS is useful for droplet sizes around or near 50 nm, and we compare its advantages and disadvantages with those of emulsions. We also cover the criteria for selecting excipients such as oil, surfactant, and solvents for the groundwork of SEDDS and SMEDDS. In addition, we discuss the methods of preparation of emulsions and their characterization. Finally, we examine the different techniques for solidifying liquid/semisolid emulsions into solid preparations along with their advantages and disadvantages. We conclude with a list of dosage forms for oral administration. This review provides a comprehensive analysis of the solubility properties of compounds, focusing on the different approaches to enhance solubility for more efficient action. We also delve into the common variables that affect solubilities, including polarity, polymorphs, molecular size, temperature, pressure, countryside of the solute and solvent, and particle magnitude. To overcome these solubility problems, various approaches have been taken to increase solubility. These include physical modification, chemical modification, and miscellaneous methods. Among these, the Self-Emulsifying Treatment Delivery Scheme (SEDDS) stands out as an efficient technique that is suitable for emulsions with droplet sizes around 100 nm to 300 nm. Furthermore, we discuss the Self-Micro Emulsifying Preparation Transfer Organization (SMEDDS), which is a further modification of SEDDS and offers advantages over emulsions. We also provide an in-depth analysis of the criteria for selecting excipients such as oil, surfactant, and solvents for the training of SEDDS and SMEDDS. In addition, we explore the methods of preparation of emulsions and their characterization. Finally, we examine the different techniques for solidifying liquid/semisolid emulsions into solid preparations, highlighting their advantages and disadvantages. We conclude with a list of dosage forms for oral administration. This review aims to provide a comprehensive guide for researchers and professionals to overcome solubility issues and enhance solubility for more efficient drug delivery.